1988
DOI: 10.1128/mcb.8.9.3943
|View full text |Cite
|
Sign up to set email alerts
|

Use of a simian virus 40-based shuttle vector to analyze enhanced mutagenesis in mitomycin C-treated monkey cells.

Abstract: When monkey cells were treated with mitomycin C 24 h before transfection with UV-irradiated pZ189 (a simian virus 40-based shuttle vector), there was a twofold increase in the frequency of mutations in the supF gene of the vector. These results suggest the existence of an enhancible mutagenesis pathway in mammalian cells. However, DNA sequence analysis of the SupF-mutants suggested no dramatic changes in the mechanisms of mutagenesis due to mitomycin C treatment of the cells.Exposure of mammalian cells to a wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1990
1990
1992
1992

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Since isolation and cloning of the genes which encode mammalian DNA repair proteins have met with little success, specific information about the formation of DNA repair complexes (in particular those involved in the repair of bulky lesions, such as UV photoproducts) and their regulation in a stress-induced environment is not yet available. Recent studies have indicated, however, that SOS-like inducible phenomena associated with DNA processing occur in mammalian cells exposed to carcinogens or tumor promoters (for a review, see references 5 and 7 and references therein; 26,29,35). Some of the proteins induced in these * Corresponding author.…”
mentioning
confidence: 99%
“…Since isolation and cloning of the genes which encode mammalian DNA repair proteins have met with little success, specific information about the formation of DNA repair complexes (in particular those involved in the repair of bulky lesions, such as UV photoproducts) and their regulation in a stress-induced environment is not yet available. Recent studies have indicated, however, that SOS-like inducible phenomena associated with DNA processing occur in mammalian cells exposed to carcinogens or tumor promoters (for a review, see references 5 and 7 and references therein; 26,29,35). Some of the proteins induced in these * Corresponding author.…”
mentioning
confidence: 99%